ELECTRONIC WORD OF MOUTH (E-WOM), STORE ATMOSPHERE DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN RUMAH MAKAN BUKIT DURIAN WONOSALAM JOMBANG - Muhammad Mahbubur Rohman; Rohmad Prio Santoso (CV. KAMPUS AKADEMIK PUBLISING, 2024)
. Research has the aim of knowing the factors that influence purchasing decisions. That is by examining several variables, namely Electronic Word of Mouth, Store Atmosphere and location at the Bukit Durian Wonosalam Jombang restaurant. Based on quantitative research by distributing questionnaires to 100 visitors at the Bukit Durian Wonosalam Jombang restaurant using the incidental sampling technique method. The findings in the study indicate (1) The level of E-WOM, Store Atmosphere and location partially influence purchasing decisions at the Bukit Durian Wonosalam Jombang restaurant (2) The level of E-WOM, Store Atmosphere and location simultaneously influence consumer decisions in making purchases at the Bukit Durian Wonosalam Jombang restaurant.